EFEKTIFITAS AROMATERAPI DAN PENDAMPING PERSALINAN TERHADAP NYERI PERSALINAN - Yuanti, Yocki; Putri, Cindy Ria Aprilia (STIKes Medistra Indonesia, 2021)
Pain is a very unpleasant sensory and emotional experience. Pain during childbirth is due to uterine contractions, cervical dilation and stretching of the pelvic floor muscles. The purpose of this study was to explain the contribution of presenting aromatherapy to labor pain with the accompanying labor variable. The research design was non-experimental with a cross sectional study approach. The population was all mothers who gave birth at the Nanggung Public Health Center on 24 February - 14 March 2020. The sampling technique was accidental sampling of 40 people. Data using Chi Square test and Multiple Logistic Regression with risk factor analysis model. The results showed that 65% of the mothers who experienced mild labor pain were in labor. The provision of aromatherapy had a significant contribution to labor pain in laboring mothers (p-value 0.014) with an OR of 6.768, while delivery companions did not have a significant contribution to labor pain in laboring mothers (p-value 0.127). The provision of aromatherapy during childbirth is highly recommended to manage the pain caused by the delivery process and it is important for midwives to support mothers who give birth in managing a safe and comfortable birth experience, minimal trauma both psychological and physiological.